94‐GHz 360° reflective‐type phase shifter with minimal loss variation using triple‐resonating load technique. Issue 4 (1st February 2018) - Gu, Peng; Zhao, Dixian
Abstract : This Letter reports a 360° reflective‐type phase shifter in 100‐nm InGaAs pHEMT technology. A triple‐resonating load technique is proposed and the optimum conditions are derived to achieve full 360° phase‐shift range and minimise the insertion loss variation. The implemented reflective‐type phase shifter achieves a measured phase‐shift range of 360° and an insertion loss of 9.0 ± 0.9 dB at 94 GHz. Measured return loss is better than 14 dB across 360° phase‐shift range.